The Impact of Specialised Professional Accountancy Implications on accounting Research: A Future Concern: Examining the Impact of Specialised Professional Accountancy on Accounting Research (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Specialized or Professional accounting are being interpreted as an area of accounting, as defined by the governing professional association of accountants, and is handled by accounting practitioners in that sector.The article addresses the potential impact of accounting curriculum and accounting specialist societies in the discussion on the profile and standard of accounting education research. This study analyses the main financial reporting professional societies in India. The piece makes a substantial background by applying the principle of institutional logic to the literature on professional accounting associations (PAAs) showing the prevailing commercial logic of the educational function and the more conventional fiduciary logic of the Professional function. Investigation has shown that the key players in the vocational financial reporting curriculum development strategy are PAAs and employers, while the accounting profession is conspicuously absent.The relative autonomy of curriculum and research and professional roles throughout PAAs is often established professional research and technological practises have little impact on vocational education and inversely. Moreover, PAA support for academic study is popular in many countries for brand identification and, in some cases, to control legislation instead of instruct professional curriculum materials.These analysis may facilitate stakeholders in assessing the results of specialized accounting in emerging and developed economies and guide potential interventions. The minimal research studies examining the relationship between PAOs and accounting research and offers perspectives from two roundtables facilitated by the International Accounting Education and Research Association. Developers define possibilities for study and concerns for research design. We hope this work will promote the advancement of this literature by accounting researchers.